2003
DOI: 10.1002/mame.200390002
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Response to Organic Vapor of Conductive Composites from Amorphous Polymer/Carbon Black Prepared by Polymerization Filling

Abstract: In recent years, conductive polymer composites have found applications as gas sensors because of their sudden change in electric resistance of several orders of magnitude when the materials are exposed to certain solvent vapors. However, the composites having this function reported so far are mostly based on crystalline polymeric matrices, which factually sets a limit to materials selection. The present work prepares polystyrene/carbon black composites through polymerization filling and proves that the amorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…polymerization filling, that is, in-situ polymerization of the monomers in the presence of the conducting fillers. [9] Grunlan et al used particulate polymer starting materials (i.e., latex and water-dispersible powder) and prepared CB/ poly(vinyl acetate) (PVAc) composites with a percolation threshold near 2.5 vol.-% of CB. [10] In fact, their technical route is based on a nonrandom segregated distribution of CB particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…polymerization filling, that is, in-situ polymerization of the monomers in the presence of the conducting fillers. [9] Grunlan et al used particulate polymer starting materials (i.e., latex and water-dispersible powder) and prepared CB/ poly(vinyl acetate) (PVAc) composites with a percolation threshold near 2.5 vol.-% of CB. [10] In fact, their technical route is based on a nonrandom segregated distribution of CB particles.…”
Section: Introductionmentioning
confidence: 99%
“…By examining the above works, it is found that (i) the reduction of the dimensionality of the conduction pathways, for example, by placing CB in a two-dimensional space such as an interface of the components using the concept of segregated structure, [7] and (ii) improvement of the intimate contacts between CB and the matrix, [9] are critical for significantly decreasing the percolation threshold. According to these mechanisms, the authors of the present work used waterborne polyurethane (WPU) latex as a matrix to explore the possibility of reducing the conduction percolation of CB in binary composites.…”
Section: Introductionmentioning
confidence: 99%
“…The electric resistance measurements, the investigation of its vapor-sensing performance and detecting device were all performed in accordance with our previous work (Li et al 2003b). The electrical response of the composites to organic solvent vapors was measured by hanging the electrode coated with composites film in a glass conical flask containing pure solvent (methanol, ethanol, acetone, chloroform, benzene, and phenixin) at the bottom.…”
Section: Vapor-sensing Performance Testmentioning
confidence: 99%
“…In this context, lower molecular weight matrix would result in higher responsivity to organic vapors instead. 19 Therefore, there would be an optimum molecular weight specified for each polymer serving as the matrix of the chemisensor. In other words, the matrix polymer of conducting composites used as gas sensors should possess appropriate molecular weight to ensure sufficiently high response and response rate.…”
Section: Solution-blended Cb/pmma Compositesmentioning
confidence: 99%
“…Narkis et al 8,17 indicated that the sensitivity of carbon black filled immiscible polymer blends to organic solvents depends on blending composition, nature of the constituting components, interfacial feature, and production shear level. In our previous works, [18][19][20] polymerization filling was employed to synthesize amorphous polymers based composites, which exhibit sufficient vapor sensibility and reproducibility. The content of carbon black, testing temperature and organic solvent species exert important influences on the electrical response of the composites.…”
mentioning
confidence: 99%